The Feasibility Analysis of Marketing, Technical, and Financial Aspects of the Production of Mocca Flavored Solid Brem (Case Study on Small Industry of Brem â€œPrihantiniâ€ Caruban, Madiun) - Cahyu, Beriska; Wignyanto, Wignyanto; Sucipto, Sucipto (Fakultas Teknologi Pertanian Universitas Brawijaya, 2008)
This research was aimed to find out feasibility of marketing, technical, and financial aspects in producing mocca added solid brem. Â The method used in this research was descriptive analysis. The observed variables of marketing aspect comprised of potential market of solid brem in the future and the growth of population at the marketing regions. The checked variables of technical aspect covered production capacity design, processing unit design, and determination of required machines and equipment. Â The assessed variables of financial aspect consisted of capital requirement, income estimation, and financial feasibility.Â The result of the research showed that the requested forecasting analysis of solid brem in 2002-2006 followed the equation of Y= 12568+268(X) and increased to 3.2% in 2008. The result of technical aspect showed that the production capacities increased to 10% and it was predicted to be 14640 boxes per year and the production ratio of the original brem to the mocca flavored brem was 90%:10%. The improvement of the production capacities caused the increase in the time of tape production to 10 minutes and brem production to 1 hour and 10 minutes. Â The result of financial analysis showed the production cost of the original brem was Rp 61.479.519,- and the mocca flavored brem was Rp 6.824.578,-. Â The Selling price for the original brem was Rp 6.500,- with mark up of 40%, while mocca flavored brem was Â Rp 7.500,- with mark of 47%. Â Break Event Point for mocca flavored brem was 528 box. Â The mocca addition gave the benefits of 6.8%, and it was more than original brem.Keywords: feasibility analysis, technical aspect, marketing aspect, financial aspect, solid brem, mocca flavor